2014
DOI: 10.1074/jbc.m113.515890
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Cholesterol Regulates Ubiquitination and Degradation of the Cholesterol Export Proteins ABCA1 and ABCG1

Abstract: Background: Cholesterol transporters ABCA1 and ABCG1 export excess cellular cholesterol and protect against atherosclerosis. Results: Cholesterol loading decreases cellular degradation of ABCA1 and ABCG1 and also their ubiquitination. Conclusion: Cholesterol-dependent suppression of ABCA1 and ABCG1 ubiquitination decreases their proteasomal degradation. Significance: This mechanism enhances the capacity of cholesterol-loaded cells to export their excess cholesterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 54 publications
9
44
0
1
Order By: Relevance
“…According to previous studies, proteasome-and lysosomemediated degradation are the major pathways responsible for ABCA1 and ABCG1 protein stability (32)(33)(34)(35). The present study found that visfatin caused protein instability of ABCG1 through the proteasome-mediated degradation pathway (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…According to previous studies, proteasome-and lysosomemediated degradation are the major pathways responsible for ABCA1 and ABCG1 protein stability (32)(33)(34)(35). The present study found that visfatin caused protein instability of ABCG1 through the proteasome-mediated degradation pathway (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Unexpectedly, the upregulation of ABCA1 expression by apoptotic GCs required the endogenous TXLNA in SCs (Figure 5d). ABCA1 degradation is mediated through ubiquitination, 21 which was evidenced in our study that 6-h incubation with apoptotic GCs substantially abolished ABCA1 ubiquitination in SCs (Figure 5e). However, in TXLNA-deficient SCs (Figure 5f), ABCA1 ubiquitination was constantly observed regardless of the presence of apoptotic GCs (Figure 5g).…”
Section: Resultssupporting
confidence: 54%
“…38,39 (iii) Ubiquitination has been associated with lysosomal degradation of cell surface-resident ABCA1 in HuH-7 and THP-1 macrophages. 21 (iv) Accumulated data evidence a frequent participation of ubiquitination in the metabolism of syntaxin. 40 By using an antibody-based ubiquitome analysis, Na et al 41 have demonstrated that a large number of synaptic proteins are modified by ubiquitination.…”
Section: Discussionmentioning
confidence: 98%
“…Our results suggest that NOD2 signaling causes intracellular lipid accumulation by promoting increased uptake of oxidized LDL probably through upregulation of scavenger receptors, but also by inhibiting HDL-mediated cholesterol efflux possibly through downregulation of ABCA1 in macrophages. The bell-shaped modulation of ABCA1 abundance by MDP is most likely a result of combination of the effects of increased cellular cholesterol content [32] due to increased uptake of oxidized LDL at low MDP concentrations and direct downregulation of ABCA1 at high MDP …”
mentioning
confidence: 99%